ADAPTASI PADA MAHASISWA SOSIOLOGI FISIP UNIVERSITAS RIAU TERHADAP SISTEM DARING - Jihad Makrufi Mustian; Risdayati " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
This research is entitled "Adaptation of Sociology FISIP Riau University Students to the Online System." The purpose of this study was to determine the adjustment made and the supporting and inhibiting factors experienced by Sociology FISIP Riau University students towards online system adaptation. The research approach used is quantitative research with descriptive methods. The data collection technique is to distribute questionnaires with the google form media platform. Based on the research results, there are two types of adaptation applied by Sociology FISIP Riau University students: conformity adaptation and innovation adaptation. In addition, there are three supporting factors for adapting the online system experienced by students and lecturers: an advanced formal education system, future orientation, and community dissatisfaction with specific areas of life. Students and lecturers experience two inhibiting factors: slow development science and very traditional attitudes of society. Keyword: Adaptation, Online Systems, Conformity, Innovation